International legal basis of application of the Armed Forces of Ukraine abroad and problems of implementation as an example peacekeeping operations in Yugoslavia and Iraq - Лисак, Ярослав Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
Article is devoted to the legal framework of Ukraine's participation in international peacekeeping activities, analysis of international instruments of the United Nations, NATO, the last few years to maintain international peace and security. Analyzes the legal basis for the use of the Armed Forces of Ukraine for example peacekeeping operations in Yugoslavia and Iraq.